De la potestad sancionatoria estatal frente a la omisión al deber de implementación de las NIIF (2015)
This article analyzes the performance of the Colombian state sanctioning authority facing the omission of the duty to implement IFRS. Articles 9 and 10 of Law 1314 of 2009 stipulated the administrative authorities may impose sanctions on those that may be * El presente artículo surgió como reflexión a propósito de la pasantía internacional y opción de grado, Implementación NIIF-NIC, Ciudad de México, octubre de 2014. ** Estudiante de décimo semestre del pregrado en Contaduría Pública, Universidad del Quindío. reluctant to IFRS provisions, they are: legal persons (economic entities) and individuals (its directors, officers and information assurance professionals).